Amino Acid Trp: The Far Out Impacts of Host and Commensal Tryptophan Metabolism - Grifka-Walk, Heather M.; Jenkins, Brittany R.; Kominsky, Douglas J. (Frontiers in Immunology, 2021)
Tryptophan is an essential amino acid primarily derived from the diet for use by the host for protein synthesis. The intestinal tract is lined with cells, both host and microbial, that uptake and metabolize tryptophan to also generate important signaling molecules. Serotonin (5-HT), kynurenine and its downstream metabolites, and to a lesser extent other neurotransmitters are generated by the host to signal onto host receptors and elicit physiological effects. 5-HT production by neurons in the CNS regulates sleep, mood, and appetite; 5-HT production in the intestinal tract by enterochromaffin cells regulates gastric motility and inflammation in the periphery. Kynurenine can signal onto the Aryl Hydrocarbon Receptor to elicit pleiotropic responses from several cell types including epithelial and immune cells, or can be further metabolized into bioactive molecules to influence neurodegenerative disease. There is a remarkable amount of cross-talk with the microbiome with regard to tryptophan metabolites as well. The gut microbiome can regulate the production of host tryptophan metabolites and can use dietary or recycled tryptophan to generate bioactive metabolites themselves. Tryptophan derivatives like indole are able to signal onto xenobiotic receptors, including AHR, to elicit tolerogenic effects. Here, we review studies that demonstrate that tryptophan represents a key intra-kingdom signaling molecule.